JUDICIAL REVIEW UNDANG-UNDANG PERKAWINAN: FLOATING EXECUTION MAHKAMAH KONSTITUSI DAN IMPLIKASINYA TERHADAP KEPASTIAN HUKUM - Fattah, Mohammad; Mustaufiy, Ahmad Syagif Hannany (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2024)
The Constitutional Court's decisions are not always implemented. This is proven by two Constitutional Court decisions in reviewing the Marriage Law (hereinafter written as UUP) which was "floating" (floating execution). In other words, it was not followed up with changes to norms as mandated in the Constitutional Court decision. The two decisions in question are Decision Number 46/PUU-VIII/2010 and regarding the birth of illegitimate children and Decision Number 69/PUU-XIII/2015 regarding marriage agreements. The two decisions above both cancel several articles in the UUP. Decision number 46/PUU-VIII/2010 annulled Article 43 paragraph (1) of the UUP which limits the civil relations of illegitimate children to only the mother and her mother's family. Meanwhile, in decision number 69/PUU-XIII/2015, the Constitutional Court annulled the provisions in Article 29 paragraph (3) of the UUP regarding marriage agreements which are only limited to the time before the marriage takes place. This research aims to trace the ratio decidendi in the Constitutional Court's decision regarding the judicial review of UUP, analyze the Constitutional Court's decision through al-qawaid al-fiqhiyyah al-qadhaiyyah, analyze the existence of juridical legal norms in UUP which were annulled by the Constitutional Court in relation to legal certainty and reconstruct the Constitutional Court's ideal relationship with executive and legislative powers so as to produce legal decisions that are implementable. Methodologically, this research seeks to analyze the prescriptive justification for three "floating" MK decisions. Therefore, this research is classified as doctrinal legal research which focuses on the rules of necessity (das sollen). Thus, the primary data sources in this research are the three Constitutional Court decisions in question, namely Decision Number 46/PUU-VIII/2010 concerning illegitimate children and Decision Number 69/PUU-XIII/2015 concerning marriage agreements. The results show that there are checks and balances, in this case, that is, each branch of power can supervise and balance so that no state institution is supreme. Therefore, the emphasis of the separation of powers is to clarify the position of each branch of power in carrying out its constitutional functions, and ultimately, to avoid overlapping between existing authorities.